Women’s alcohol consumption and cumulative incidence of live birth following in vitro fertilization - Dodge, L. E. (J Assist Reprod Genet, 2017)
OBJECTIVE: The objective of this study was to determine the effect of alcohol consumption on outcomes among women undergoing in vitro fertilization (IVF). DESIGN: This study is a retrospective cohort study. SETTING: This study was performed in a private academically affiliated IVF center. PATIENTS: Patients included women presenting for their first IVF cycle from July 2004 through October 2012. INTERVENTION: Women completed self-administered questionnaires before their first IVF cycle, which included report of usual alcohol consumption. Women were categorized as non-drinkers, social drinkers, or daily drinkers, as well as by the number of drinks consumed per week. Competing risks analysis was used to calculate the cumulative incidence of live birth after 6 cycles stratified by alcohol consumption. MAIN OUTCOME MEASURES: Main outcome measures included spontaneous abortion, clinical pregnancy, and live birth following IVF. RESULTS: There were 591 (27.7%) non-drinkers, 1466 (68.7%) social drinkers, and 77 (3.6%) daily drinkers (total n = 2134). In the first cycle, compared to non-drinkers, daily drinkers had a twofold increased risk of spontaneous abortion (adjusted risk ratio [aRR] 2.2; 95% confidence interval [CI] 1.1–4.5) among all cycle starts, and while their risk of live birth was 30% lower (aRR 0.7; 95% CI 0.4–1.3), the sample size was small, and it was not significantly lower. By the end of 6 cycles, social drinkers and daily drinkers did not differ from non-drinkers in their cumulative incidence of live birth (56.1, 50.6, and 52.1%, respectively; both P ≥ 0.28). CONCLUSION: There was a trend towards lower risk of live birth among daily drinkers. Daily drinkers had an increased risk of spontaneous abortion in the first cycle, but the number of daily drinkers was small. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10815-017-0923-5) contains supplementary material, which is available to authorized users.